Barriers, facilitators, strategies and outcomes to engaging policymakers, healthcare managers and policy analysts in knowledge synthesis: a scoping review protocol. Issue 12 (23rd December 2016) - Tricco, Andrea C; Zarin, Wasifa; Rios, Patricia; Pham, Ba'; Straus, Sharon E; Langlois, Etienne V
Abstract : Introduction: Engaging policymakers, healthcare managers and policy analysts in the conduct of knowledge synthesis can help increase its impact. This is particularly important for knowledge synthesis studies commissioned by decision-makers with limited timelines, as well as reviews of health policy and systems research. A scoping review will be conducted to assess barriers, facilitators, strategies and outcomes of engaging these individuals in the knowledge synthesis process. Methods and analysis: We will follow the Joanna Briggs Institute guidance for scoping reviews. Literature searches of electronic databases (eg, MEDLINE, EMBASE, Cochrane Library, ERIC, PsycINFO) will be conducted from inception onwards. The electronic search will be supplemented by searching for sources that index unpublished/difficult to locate studies (eg, GreyNet International database), as well as through scanning of reference lists of reviews on related topics. All study designs using either qualitative or quantitative methodologies will be eligible if there is a description of the strategies, barriers or facilitators, and outcomes of engaging policymakers, healthcare managers and policy analysts in the knowledge synthesis process. Screening and data abstraction will be conducted by 2 team members independently after a calibration exercise across the team. A third team member will resolve all discrepancies. We will conduct frequency analysis and thematic analysis to chart and characterise the literature, identifying data gaps and opportunities for future research, as well as implications for policy. Ethics and dissemination: This project was commissioned by the Alliance for Health Policy and Systems Research, WHO. The results will be used by Alliance Review Centers of health policy and systems research in low-income and middle-income countries that are conducting knowledge synthesis to inform health policymaking and decision-making. Our results will also be disseminated through conference presentations, train-the-trainer events, peer-reviewed publication and a 1-page policy brief that will be posted on the authors' websites.